PROFIL PENDERITA SEPSIS AKIBAT BAKTERI PENGHASIL ESBL - Irawan, Danny; -, Hamidah; -, Purwati; EA, Triyono; -, Bramantono; V, Arfianto; U, Hadi; -, Nasronudin; -, Suharto; E, Soewandojo (journal of internal medicine; Vol. 13, No. 1 Januari 2012, 2014)
Extended Spectrum !-Lactamases (ESBL) is plasmid enzyme which catalyzing hydrolysis and inactivation !-lactam antibiotic, including third generation of Cephaloporin, penicillin and aztreonam. This enzyme is mutation of !-lactamase TEM-1, TEM-2, and SHV-1 which commonly found in Enterobacteriaceae and normally have resistance to penisillin and rst generation celaphorin. The incidence of infection cause by ESBL bacterial is increasing worldwide. Antimicrobial Resistance in Indonesia: prevalence and prevention (AMRIN study) is showed incidence of infection ESBL bacterial 29% E. coli, and 36% K. pneumonia. This study is descriptive and restrospectively learn about prole of DMK with septicemia patient caused by ESBL bacterial in Internal Medicine Ward RSUD Dr Soetomo within 1st January 2010 until 30th June 2011. Sixty four patient were recruited and 48 patients with ESBL bacterial positive. Mortality rate is 16.7%, severe septic condition 27.08%, septic shock 14.58%. The result of positive ESBL bacterial was found from urine culture (37.5%). Sensitivity of antibiotics results are meropenem (98.07%), amikacin (88.46%).
Keywords: ESBL, antibiotic, sensitivity